Adiposity, metabolites, and colorectal cancer risk: Mendelian randomization study - Bull, Caroline J.; Bell, Joshua A.; Murphy, Neil; Sanderson, Eleanor; Davey Smith, George; Timpson, Nicholas J.; Banbury, Barbara L.; Albanes, Demetrius; Berndt, Sonja I.; Bézieau, Stéphane; Bishop, D. Timothy; Brenner, Hermann; et al. (BMC medicine, 2020)
Higher adiposity increases the risk of colorectal cancer (CRC), but whether this relationship varies by anatomical sub-site or by sex is unclear. Further, the metabolic alterations mediating the effects of adiposity on CRC are not fully understood.